A preliminary study on the main insect pests associated with a date palm Phoenix dactylifera in the western part of Saudi Arabia - Alshehri, Hassan (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2022)
Knowledge of ecological aspects of insect pests is one of the most important portions for applying the integrated pest management. This study was conducted to survey the main insect pests of date palms in the Agricultural Research Station, affiliated to King Abdul-Aziz University, which is located in Huda Al-Sham region, western Saudi Arabia as a preliminary study in this region. In this field, insects were bimonthly collected by using light and pitfall traps starting from 1/1/2020 to 30/12/2020. Results showed that date palms were infested by seven pests including the palm stem borer beetle Oryctes elegans, the red palm weevil Rhynchophorus ferrugineus, the cadelle beetle Tenebroides mauritanicus, the palm frond borer Phonapate frontalis, the bluegrass billbug Sphenophorus parampunctatus, the desert locust Schistocerca gregaria and the island pinhole borer Xyleborus perforans. However, the island pinhole borer X. perforans was found to be the dominant species (5730 individuals) in the abundance compared to the other species, whereas the desert locust Schistocerca gregaria was found to be a much rarer species (21 individuals). The results of this study could be useful for managing date palm pests under harsh climate conditions.